Afterlives of War : A Descendants' History - Michael Roper (Manchester University Press, 2023)
Afterlives of war documents the lives and historical pursuits of the generations who grew up in Australia, Britain and Germany after the First World War. Although they were not direct witnesses to the conflict, they experienced its effects from their earliest years. Based on ninety oral history interviews and observation during the First World War Centenary, this pioneering study reveals the contribution of descendants to the contemporary memory of the First World War, and the intimate personal legacies of the conflict that animate their history-making.